Comparative Architecture and Algorithm Study for Energy-aware Social Networking Virtualized Data Centers - Oza, Prashantkumar; Kamdar, Dipesh; Patel, Nikhil (International Journal of Computer Sciences and Engineering, 2019)
Cloud computing is an internet based computing technology that provide on demand computing for end users. Normally, data centers allocation for application on statically based. But today so many data centers have a problem how to reduce energy consumption? Due to increase use of cloud services and infrastructure by various cloud providers, uses of energy day by day increase that’s why energy consumption increase lots. Large numbers of data centers that consume lots of energy which increase the level of co2. For decrease energy consumption of data centers need to develop efficient VM migration algorithm which will provide utilization of the VM. Energy conservation then becomes essential, in order to decrease operation costs and increase the system reliability. Using VM consolidation and VM migration data centers per- form efficient energy saving. In this paper discuss Comparative Architecture and Algorithm Study for Energy-aware Social Networking Virtualized Data Centers.